Resting metabolic rate and anthropometry in older people: a comparison of measured and calculated values. Issue 1 (14th February 2014) - Reidlinger, D. P.; Willis, J. M.; Whelan, K.
Abstract Background Accurate assessment of energy expenditure and anthropometry in older people is important for targeted nutritional support. The present study aimed to compare measured and calculated resting metabolic rate (m‐RMR and c‐RMR) and measured, calculated and estimated weight and height in older people aged ≥70 years. Methods Participants were healthy older people aged ≥70 years. Indirect calorimetry using a ventilated hood calorimeter was performed for 30 min on fasted participants, and was compared with c‐RMR, as calculated using six commonly used equations. Measured, calculated and estimated height and weight were compared. Results Subjects comprised 14 males and 20 females and mean (SD) m‐RMR was 5243 (845) kJ day−1 [1253 (202) kcal day−1]. The Mifflin St‐Jeor equation was the most consistently accurate, with the smallest mean difference between m‐RMR and c‐RMR of 58 (553) kJ day−1 [14 (132) kcal day−1] and c‐RMR was within 10% of m‐RMR in the greatest number of participants (n = 24; 70%). The Schofield equation was among the least accurate in this age group. In older males, self‐reported height and weight were accurate, whereas, in females or those unable to self‐report height, ulna length was the most accurate alternative to measured height. Conclusions Current equations used to calculate RMR in older people have inaccuracies, although the Mifflin St‐Jeor equation was most accurate. Future studies should investigate the validity, reliability, cost and practicality of using fat free mass as an item in novel equations to calculate RMR in this age group. Self‐reported height and weight in males, and height calculated from ulna length in females, were the most accurate alternatives to measured values in the present study.